Shifting Paradigms: Thomas S. Kuhn and the History of Science - Christian Joas (ed.) (Proceedings 8: Max Planck Research Library for the History and Development of Knowledge, 2016)
The publication of Thomas S. Kuhn's "Structure of Scientific Revolutions" in 1962 stands for a turning point in the history and philosophy of science. The repercussions of this work have rearticulated the theoretical framework of history and philosophy of science and have also generated discussions that contributed to the formation of the communities of historians as well as philosophers of science in many parts of the world. Different approaches to history of science have since emerged and most of them have the "Structure" as their reference point. In October 2012, a conference at the Max Planck Institute for the History of Science brought together some of the historians of science whose work has played a decisive role in the ways history of science has evolved as a field of research in the past 50 years, both intellectually and institutionally. This volume gathers reflections by many of these historians on the history of the history of science, based on the presentations and discussions at the conference. The topics covered range from personal recollections of working with Thomas Kuhn to broad overviews of the historical development of the history of science as a discipline in the past half-century. The series Proceedings of the Max Planck Research Library for the History and Development of Knowledge presents the results of scientific meetings on current issues and supports further cooperation on these issues via an electronic platform. The volumes are available both as print-on-demand books and as open-access publications on the Internet. The material is freely accessible online at www.edition-open-access.de.